Determinant Factors of Lung Tuberculosis in North Sumatera Province: Analysis of Indonesia Health Survey Data 2023 - Agil Lauchan; Yulia Khairina Ashar; Putra Apriadi Siregar; Hasrat Efendi Samosir (Poltekkes Kemenkes Surabaya, 2025)
Pulmonary Tuberculosis disease is a chronic, contagious infection that remains a global public health challenge today. Indonesia ranks as the country with the second highest number of pulmonary TB cases in the world, behind India and followed by China. North Sumatra Province is ranked third in Indonesia for the highest burden of pulmonary TB after West Java and East Java with an estimated case of 74,434 cases in 2024. The purpose of the study was to analyze the determinant factors and the most influential factors and see the probability prediction of the incidence of Lung Pulmonary Tb in North Sumatra Province based on the 2023 Indonesian Health Survey (IHS) data. This research is a type of quantitative method research with a cross sectional design. The sample size in this study was 54,397 respondents. Data were analyzed through univariate, bivariate, and multivariate approaches by applying logistic regression tests. Based on the results of the study, there are factors that influence the incidence of Pulmonary TB in North Sumatra Province, namely gender factors, age factors, lighting factors, and nutritional status factors with a value of (p = <0.05). The multiple logistic regression test showed that the age factor was the most dominant factor associated with the incidence of Pulmonary TB in North Sumatra Province with a value of (OR = 3.976, 95% CI = 2.105 - 7.521). The probability of developing pulmonary TB if all risk factors such as male gender, productive age, inadequate lighting, and poor nutritional status are present is 65.3%. This study is expected to provide a comprehensive picture of the factors that contribute to the incidence of Pulmonary TB in North Sumatra Province, so that it can be the basis for formulating strategies for prevention and control of this disease.